Proceedings of the 2nd International Symposium on Transportation Studies in Developing Countries (ISTSDC 2019) 2020
DOI: 10.2991/aer.k.200220.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Factors Influencing the Evacuation Walking Speed in Padang, Indonesia

Abstract: This paper aims to identify factors influencing the walking speed of evacuees by conducting an evacuation drill in Padang, West Sumatera, Indonesia. A number of 18 volunteers and 6 observers, were gathered in an evacuation experiment on 3 routes with 5 segments each. The chosen routes are almost equal in terms of distance, but different in terms of the number of turning points. The experiment comprises of three cases in terms of the complexity of the route. These cases represent a simple, a medium and a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The special contribution of this paper was integration between horizontal evacuation from home to a shelter and vertical evacuation from the ground of the shelter building to the top of the building either through a ramp or a stair. This paper is an extension of our previous study which observed the walking speed of evacuees during an experiment of tsunami evacuation in Padang [15].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The special contribution of this paper was integration between horizontal evacuation from home to a shelter and vertical evacuation from the ground of the shelter building to the top of the building either through a ramp or a stair. This paper is an extension of our previous study which observed the walking speed of evacuees during an experiment of tsunami evacuation in Padang [15].…”
Section: Introductionmentioning
confidence: 77%
“…In a previous study, the variation of the walking speed was observed by age and by gender [6,28,29]. Yosritzal suggested adding the duration of the walk and the complexity of the route as a determinant of the walking speed [15]. Yosritzal developed three scenarios in the evacuation drill which were based on the complexity of the route [15].…”
Section: Walking Speed Studies In Disaster Evacuationmentioning
confidence: 99%
See 2 more Smart Citations
“…The author argued that this movie clip was a tool to help experts establish scenario-based evacuation strategies and to implement preparedness activities for non-expert citizens. In the same year, Yosritzal et al (2020) conducted an evacuation drill to analyze the effects on walking speed from age, gender, and walking distance in a community in Indonesia. The authors assigned six observers to record the travel time for 18 evacuees on three designed evacuation routes.…”
Section: Evacuation Drillmentioning
confidence: 99%